The development of fuel cell electric vehicles – A review. (2021) - Muthukumar, M.; Rengarajan, N.; Velliyangiri, B.; Omprakas, M.A.; Rohit, C.B.; Kartheek Raja, U.
Abstract: The natural petroleum by-product will come into in-existence and unavailable in future. The emission from IC engine vehicles is also a critical problem. So the new technologies depending on electrical powered conveyance are developing. In that way, a fuel cell concept has been introduced for various applications along with electric vehicles. The various efforts are being taken to implement the fuel cell systems in automobiles. Still there is a technological gap in success of such fuel cell electric vehicles due to the problem in handling hydrogen, high cost of battery and fuel cell components, water management etc. In this paper, the type of fuel cell used in automobile, various supporting components and flow diagram of fuel cell systems, the implementation of fuel cell systems in automobiles, the design and development of Fuel Cell Electric Vehicles (FCEV) by various automobile companies are discussed. Further the related issues in FCEV and the methods to improve performance of FCEV are discussed.